Radiographic and Clinical Outcomes of the Salto Talaris Total Ankle Arthroplasty. (December 2020) - Day, Jonathan; Kim, Jaeyoung; O'Malley, Martin J.; Demetracopoulos, Constantine A.; Garfinkel, Jonathan; Sanders, Austin; Roney, Andrew; Deland, Jonathan T.; Levine, David S.; Ellis, Scott J.
Background: The Salto Talaris is a fixed-bearing implant first approved in the US in 2006. While early surgical outcomes have been promising, mid- to long-term survivorship data are limited. The aim of this study was to present the survivorship and causes of failure of the Salto Talaris implant, with functional and radiographic outcomes. Methods: Eighty-seven prospectively followed patients who underwent total ankle arthroplasty with the Salto Talaris between 2007 and 2015 at our institution were retrospectively identified. Of these, 82 patients (85 ankles) had a minimum follow-up of 5 (mean, 7.1; range, 5-12) years. The mean age was 63.5 (range, 42-82) years and the mean body mass index was 28.1 (range, 17.9-41.2) kg/m 2 . Survivorship was determined by incidence of revision, defined as removal/exchange of a metal component. Preoperative, immediate, and minimum 5-year postoperative AP and lateral weightbearing radiographs were reviewed; tibiotalar alignment (TTA) and the medial distal tibial angle (MDTA) were measured to assess coronal talar and tibial alignment, respectively. The sagittal tibial angle (STA) was measured; the talar inclination angle (TIA) was measured to evaluate for radiographic subsidence of the implant, defined as a change in TIA of 5 degrees or more from the immediately to the latest postoperative lateral radiograph. The locations of periprosthetic cysts were documented. Preoperative and minimum 5-year postoperative Foot and Ankle Outcome Score (FAOS) subscales were compared. Results: Survivorship was 97.6% with 2 revisions. One patient underwent tibial and talar component revision for varus malalignment of the ankle; another underwent talar component revision for aseptic loosening and subsidence. The rate of other reoperations was 21.2% ( n = 18), with the main reoperation being exostectomy with debridement for ankle impingement ( n = 12). At final follow-up, the average TTA improved 4.4 (± 3.8) degrees, the average MDTA improved 3.4 (± 2.6) degrees, and the average STA improved 5.3 (± 4.5) degrees. Periprosthetic cysts were observed in 18 patients, and there was no radiographic subsidence. All FAOS subscales demonstrated significant improvement at final follow-up. Conclusions: We found the Salto Talaris implant to be durable, consistent with previous studies of shorter follow-up lengths. We observed significant improvement in radiographic alignment as well as patient-reported clinical outcomes at a minimum 5-year follow-up. Level of Evidence: Level IV, retrospective case series.